La inserción de la República Popular China en el noreste asiático desde los años 1970: ¿hacia un nuevo regionalismo? (2008)
The following research has as a main objective to carry on a detailed and deep analysis about the People’s Republic of China and the relationship with its neighboring countries in the Northeast Asian region –Japan, North Korea, South Korea and Taiwan- at historical level, having the 15th century as a starting point, but mainly focusing in the development of such relationships from 1970 up to the first decade of the 21st century, in order to understand Beijing’s dynamics and strategies as a new emerging power during its insertion process in the region after the 1978 economical reforms, and the new tendencies towards a new regionalism which China intends to lead. The project analyzes several Colombian authors who have previously developed related issues and are considered somehow relevant for this work. Furthermore, it incorporates some of the international relations paradigms in the Northeast Asian context, helping to build a theoretical framework. In addition, the project looks into the most important historical episodes that took place in the countries under study, in order to have a deeper understanding of the facts that have led to the current scene in the area. After that, the text goes through the main factors that have caused either disintegration or rapprochements between China and the other three concerned States, from 1970 up to the present, which somehow have shaped the foreign policy of each country involved. Finally the research analyzes the integration process that has taken place in the Northeast Asia region and the main regionalism tendencies and initiatives.